Synchronized, Spontaneous, and Oscillatory Detachment of Eukaryotic Cells: A New Tool for Cell Characterization and Identification. Issue 24 (3rd July 2022) - Yongabi, Derick; Khorshid, Mehran; Losada‐Pérez, Patricia; Bakhshi Sichani, Soroush; Jooken, Stijn; Stilman, Wouter; Theßeling, Florian; Martens, Tobie; Van Thillo, Toon; Verstrepen, Kevin; Dedecker, Peter; Vanden Berghe, Pieter; et al.
Abstract: Despite the importance of cell characterization and identification for diagnostic and therapeutic applications, developing fast and label‐free methods without (bio)‐chemical markers or surface‐engineered receptors remains challenging. Here, we exploit the natural cellular response to mild thermal stimuli and propose a label‐ and receptor‐free method for fast and facile cell characterization. Cell suspensions in a dedicated sensor are exposed to a temperature gradient, which stimulates synchronized and spontaneous cell‐detachment with sharply defined time‐patterns, a phenomenon unknown from literature. These patterns depend on metabolic activity (controlled through temperature, nutrients, and drugs) and provide a library of cell‐type‐specific indicators, allowing to distinguish several yeast strains as well as cancer cells. Under specific conditions, synchronized glycolytic‐type oscillations are observed during detachment of mammalian and yeast‐cell ensembles, providing additional cell‐specific signatures. These findings suggest potential applications for cell viability analysis and for assessing the collective response of cancer cells to drugs. Abstract : A new method for characterizing eukaryotic cells is described. The approach is based on the observation that under a temperature gradient, eukaryotic cells display spontaneous and collective detachment from a heated solid–liquid interface. This results in an increase in the temperature of the liquid after a sharply defined time, which is temperature dependent and cell‐type specific.